A diagnostic score for anti‐myelin‐associated‐glycoprotein neuropathy or chronic inflammatory demyelinating polyradiculoneuropathy in patients with anti‐myelin‐associated‐glycoprotein antibody. (6th March 2022) - Doneddu, Pietro E.; Ruiz, Marta; Bianchi, Elisa; Liberatore, Giuseppe; Manganelli, Fiore; Cocito, Dario; Cosentino, Giuseppe; Benedetti, Luana; Marfia, Girola A.; Filosto, Massimiliano; Briani, Chiara; Giannotta, Claudia; et al.
Abstract: Background and purpose: A diagnostic score was developed to discriminate anti‐myelin‐associated‐glycoprotein (MAG) neuropathy from chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and applied it to patients with atypical anti‐MAG neuropathy. Methods: The clinical and electrophysiological features of patients with a diagnosis of typical anti‐MAG neuropathy were compared to those of patients with a diagnosis of CIDP. The association of each feature with the diagnosis was assessed in the two groups. Features showing a significant association with the diagnosis were included in a multivariable logistic regression model and adjusted odds ratios were estimated for each feature. A score ranging from 1 to 3 was applied to each feature based on the magnitude of the estimated odds ratios. The score was then applied to patients with a clinical diagnosis of CIDP who also had high anti‐MAG antibody titers (CIDP‐MAG). Results: Thirty‐one anti‐MAG neuropathy patients, 45 typical CIDP patients and 16 CIDP‐MAG patients were included. Scores in anti‐MAG antibody patients ranged from 1 to 5 and in CIDP patients from −7 to −1. Using the score, 4/16 CIDP‐MAG patients were diagnosed to have anti‐MAG neuropathy and 12/16 patients to have CIDP. Response to intravenous immunoglobulin in the CIDP‐MAG patients classified as CIDP was similar to that of definite CIDP patients and higher than that of anti‐MAG neuropathy patients. Conclusions: Our score allowed an accurate discrimination to be made, amongst patients with anti‐MAG antibodies, of those affected by CIDP and the patients with anti‐MAG neuropathy. This score may help proper treatment to be chosen for patients with anti‐MAG antibodies with a CIDP‐like presentation. Abstract : In this study, Doneddu et al. developed a score that permitted an accurate discrimination, amongst patients with anti‐myelin‐associated‐glycoprotein (anti‐MAG) antibodies, of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and patients with anti‐MAG neuropathy. This score may help in the treatment of patients with anti‐MAG antibodies with a CIDP‐like presentation.